2019
DOI: 10.21873/cgp.20116
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Targets for Therapeutic Intervention With Metastasis of Non-small Cell Lung Cancer

Abstract: The death toll of non-small cell lung cancer (NSCLC) patients is primarily due to metastases, which are poorly amenable to therapeutic intervention. In this review we focus on miRs associated with metastasis of NSCLC as potential new targets for anti-metastatic therapy. We discuss miRs validated as therapeutic targets by in vitro data, identification of target(s) and pathway(s) and in vivo efficacy data in at least one clinically-relevant metastasis-related model. A few of the discussed miRs correlate with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 175 publications
(257 reference statements)
1
41
0
Order By: Relevance
“…Multiple miRNAs have been identi ed as potential diagnostic biomarkers and therapeutic targets for NSCLC. For example, expression of miR-128-3p was signi cantly up-regulated in NSCLC tissues by comparison with adjacent normal tissues; its overexpression remarkably induced the migration and invasion of A549, Calu-3 and H520 cells [17]. In the present research, miR-199a-5p was found to be dramatically down-regulated in NSCLC tissues, serum samples of NSCLC patients and multiple NSCLC cell lines.…”
Section: Discussionsupporting
confidence: 52%
“…Multiple miRNAs have been identi ed as potential diagnostic biomarkers and therapeutic targets for NSCLC. For example, expression of miR-128-3p was signi cantly up-regulated in NSCLC tissues by comparison with adjacent normal tissues; its overexpression remarkably induced the migration and invasion of A549, Calu-3 and H520 cells [17]. In the present research, miR-199a-5p was found to be dramatically down-regulated in NSCLC tissues, serum samples of NSCLC patients and multiple NSCLC cell lines.…”
Section: Discussionsupporting
confidence: 52%
“…In recent years, with the development of molecular biology and the rise of translational medicine, novel markers and technologies are emerging for diagnosis and treatment of LUAC. [4][5][6] Circular RNAs (circRNAs) are categorized as a type of endogenous non-coding RNAs (ncRNAs) and have been regarded as transcription errors during the splicing process. Recently, accumulating evidences have revealed that circRNAs, which formed a covalent closed continuous loop without a polyadenylated tail and 5ʹ to 3ʹ polarity, are of vital significance in various cellular processions, like gene expression regulation, cell cycle progression, chromatin modification, etc.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are endogenous, small, noncoding and highly conserved RNAs 11,12 . Recent studies have revealed that miRNAs are implicated in various cellular processes [13][14][15] .…”
mentioning
confidence: 99%